IMPROVING STUDENTS' SPEAKING CONFIDENCE THROUGH ROLE-PLAY ACTIVITIES IN INDONESIAN SECONDARY ENGLISH CLASSROOMS: A MIXED-METHOD STUDY - Agus Kistian; Tursinawati Tursinawati; Muhammad Zulhairi Bin Zubairi (Sensei International Journal of Education and Linguistic, 2025)
Many students are afraid to speak English in front of the class although they already learn grammar and vocabulary. They are afraid of making mistakes and being laughed at by their friends. Role-play is one of the activities that can help the students to be more confident. This study discusses the improvement of students' speaking confidence through role-play activities. The study used a mixed-method design with an experimental class and a control class. The data were collected through a questionnaire, speaking test, observation, and interview. The result shows that the speaking confidence of the experimental class is higher than the control class and the students enjoy the activities. So, role-play can be used by the teachers to teach speaking.